Tangled worlds the story of Maria Hertogh - Hughes, Tom Eames (Institute of Southeast Asian Studies, 1980)
This story centres on the time Maria Hertogh spent in Singapore in 1950, when she became the innocent focus of a tangle of cultures and religions which aroused world-wide interest. There are introductory chapters outlining Maria's origins and an epilogue sketching what happened to her afterwards. The author was at the time head of the Singapore Social Welfare Department which was intimately involved. The account is thus largely based on firsthand knowledge